2021
DOI: 10.1088/1755-1315/762/1/012036
|View full text |Cite
|
Sign up to set email alerts
|

The effect of application of compost and frass from Black Soldier Fly Larvae (Hermetia illucens L.) on growth of Pakchoi (Brassica rapa L.)

Abstract: Pot experiment was conducted to observe the effect of frass (insect feces) from Black Soldier Fly larvae (BSFL) as soil amendments at different application rates in comparation with other organic fertilizers on Pakchoi (Brassica rapa L). The experimental design was completely random with seven treatments, namely compost, compost+LOB (liquid organic biofertilizer), 5%, 10%, and 15% BSF frass, chemical fertilizer (NPK, equivalent to 10 kg/ha), and soil as a control. After 35 days planting, the result showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 15 publications
3
17
0
Order By: Relevance
“…To varying degrees, application of HF to seedlings as a top-dressing increased shoot dry weight of seedlings in an organically-rich compost based growing medium, and two potting mixes based on garden soil, bark chips, and coir fibre. These results reinforce findings of other studies that similarly demonstrated increases in plant growth in response to application of BSFF-based fertilizers [8][9][10]12]. HF also produced similar increases in shoot growth to two other standard fertilizers, chicken manure pellets and a commercial organic fertilizer [9,13].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…To varying degrees, application of HF to seedlings as a top-dressing increased shoot dry weight of seedlings in an organically-rich compost based growing medium, and two potting mixes based on garden soil, bark chips, and coir fibre. These results reinforce findings of other studies that similarly demonstrated increases in plant growth in response to application of BSFF-based fertilizers [8][9][10]12]. HF also produced similar increases in shoot growth to two other standard fertilizers, chicken manure pellets and a commercial organic fertilizer [9,13].…”
Section: Discussionsupporting
confidence: 89%
“…These results reinforce findings of other studies that similarly demonstrated increases in plant growth in response to application of BSFF-based fertilizers [8][9][10]12]. HF also produced similar increases in shoot growth to two other standard fertilizers, chicken manure pellets and a commercial organic fertilizer [9,13].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The use of BFS larvae in composting manure increased the total P content, total N, total nutrients [12,13], and humic acid content [14], as well as reduced levels of heavy metals Ar, Cd, and Pb in compost, compared with no use of BSF larvae [13]. Several studies showed the effectiveness of BSF frass as solid organic fertilizer on several plants such as corn [15,16], ryegrass grass [17], and pak choi [18]. However, little is known about using BSF frass and leachate from the waste bioconversion process as biofertilizers.…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known about using BSF frass and leachate from the waste bioconversion process as biofertilizers. Organic residues from bioconversion by BSF larvae also contain microbes that benefit plants, such as N-fixer, P solubilizer, and phytohormones producers, which [18,19,20]. Liquid organic fertilizer produced by BSF has a high number of microbes such as Pseudomonas sp., Bacillus sp., Trichoderma harzianum, and Streptomyces sp.…”
Section: Introductionmentioning
confidence: 99%